PHONOLOGICAL FEATURES IN HARLEM HOPSCOTCH POEM BY MAYA ANGELOU - Yusup Supyani; Pajarwati, Suci (ELATICS JOURNAL, 2023)
ABSTRACT Style is an essential component of every literary work. The poem is an example of a literary work. A poem's style can be researched in many ways, one of which is through its sound. As a result, the use of sound in a poem can be utilized to determine the author's style. In the case of sound, phonology provides an overview of the language's sound system. This thesis studied about analysis of pathological features in Maya Angelou's two selected poems. This research has two objectives to discuss. First, the researcher presents phonological features found in “Harlem Hopscotsh” poem by Maya Angelou. Second, the researcher finds Maya Angelou's style in making the poems through the phonological features which are found. This research applied a stylistic approach to assess the phonological features of the poems and find Angelou's style in her poem. The population study was applied to collect the data. The researcher concludes and presents the result of phonological features analysis which consists of rhyme, meter, assonance, consonance, alliteration, and style of two poems. The suggestion of this research is to provide a comprehension to the readers and the next researchers. Keywords : Poem, Phonology, Phonological features, Stylistics